Digital input decision-making in fresh agricultural supply chains under government subsidies - He, Jing; Chen, Sixin; Zong, Chuanhong (Frontiers in Sustainable Food Systems, 2025)
IntroductionAs digital technologies advance rapidly, the digital transformation of fresh agricultural product supply chains has emerged as a critical strategy for increasing operational efficiency, reducing product waste, and maintaining constant supply. However, adoption barriers such as high costs and technical complexities highlight the crucial role of government subsidies in facilitating this transition.MethodsThis study develops an evolutionary game model to analyze interactions between suppliers and producers, incorporating: (1) government subsidies, (2) digital technology spillover effects, (3) input costs, (4) initial profit disparities, and (5) post-investment returns. The model quantifies how digital input costs affect supply chain members’ willingness to undertake digital transformation, along with the associated economic returns.ResultsKey findings demonstrate: (1) Market autonomy fails when digital costs exceed private returns, especially under high spillover effects. (2) Government subsidies effectively boost digital adoption willingness when subsidies surpass a critical threshold. (3) Higher subsidy levels and initial adoption rates accelerate supply chain transformation.DiscussionThe results demonstrate that government subsidies efficiently encourage the digital transformation of fresh agricultural supply chains. This research advances the theoretical understanding of digital transformation in agricultural supply chains and provides policymakers with decision-making tools for optimizing digital subsidy schemes in sustainable food systems.